(untitled) (GAIMS Journal of Medical Sciences, 2025)
Aim: To study the bacterial profile, along with antibiotic susceptibility pattern of isolates from suspected cases of LRTIs attending the tertiary care study area. Materials and Methods: Respiratory samples like sputum, BAL & ET secretions from patients clinically suspected with LRTIs received from both in patient and OPD of a tertiary care teaching hospital, were processed as per standard protocol in Department of Microbiology. The bacterial isolates were identified using Gram’s stain, motility and sets of biochemical tests. Antimicrobial susceptibility testing was performed and interpreted as per CLSI guidelines. Results: This was a retrospective study based on the evaluation of data from January 2023 to June 2023. A total of 1943 respiratory samples (1709 sputum, 211 ET secretions and 23 BAL) were received during the study period. 669 sputum samples (39.14%), 102 ET secretion (48.34%) and 2 BAL fluid (8.69%) were positive for bacterial isolates. Out of these 773 culture positive samples, 855 microorganisms were isolated. Klebsiella spp. was the most common isolates being 39.5% (338 isolates) followed by E. coli 23.97% (205 isolates), Pseudomonas spp. 16.9% (145 isolates), Acinetobacter spp. 14.61% (125 isolates), S. aureus 3.04% (26 isolates) and Enterococcus spp. 1.87% (16 isolates). Conclusion: Culture and susceptibility test is vital for proper diagnosis and management of patients with LRTIs. 39.78% culture positivity was observed in all the samples received with predominance of Gram-negative isolates.